Technology sharing with competitors when facing consumers with uncertain product valuation. (January 2022) - Zeng, Weijun
Highlights: Highly positively correlated consumers' valuation leads firms to technology sharing. Firms are less willing to share their technology with more risk-averse peers. Firms are more likely to share technology in Stackelberg than in Nash competition. Abstract: Risk consideration is important in firms' decision on technology sharing. However, little work has been done to explore the relationship between risk aversion of firms and their technology sharing behavior. To bridge this gap, the current study addresses effects of risk aversion of firms on their technology sharing behavior in product innovation subject to the presence of uncertainty in consumers' valuation on their products. An analytical model is presented to examine how a focal firm owning proprietary technology decides whether or not to share the technology with its competitor, who will introduce a new product that directly competes with the focal firm' s product. Specifically, the firms are engaged in a Nash or a Stackelberg game after the technology sharing. Equilibrium results indicate that, when the uncertain consumers' valuation is highly positively (or negatively) correlated for the firms' products, technology sharing becomes more (or less) likely for the focal firm who is risk averse because the risk cost associated with the uncertainty would be reduced (or increased) after the technology sharing. Furthermore, the more risk-averse is the competitor, the weaker the focal firm's incentive to share its technology in that the interfirm competition becomes fiercer after the technology sharing. Finally, the social welfare always increases with the technology sharing. These observations are true for both the Nash and the Stackelberg competitions between the firms. The results suggest that firms having products with highly positively correlated consumers' valuation can engage in technology cooperation for risk reduction; moreover, social planer should consider risk-aversion tendency of innovative firms to issue policy to promote the interfirm cooperation.